Braking index of PSR J1846−0258: a model of magnetic inclination evolution and its gravitational-wave implication - Li, Biao-Peng; Gao, Zhi-Fu; Ma, Wen-Qi; Cheng, Quan (Frontiers in Astronomy and Space Sciences, 2025)
We explain the braking index n=2.19±0.03 of PSR J1846−0258 by incorporating the time evolution of its magnetic inclination angle and dipolar magnetic field. Based on observational timing data and the age of the associated supernova remnant (tSNR≈1.77kyr), we estimate a magnetic inclination change rate of χ̇≈0.281°/100yrs, comparable to that of the Crab pulsar. Applying the two-dipole model to PSR J1846−0258, we find an internal dipole moment ratio η=M2/M1∼1026–1027. For magnetic field decay timescales τD<3.6×105 yrs, the magnetic energy dissipation rate (Ėmag∼(1033–1034) erg/s) partially explains the observed X-ray luminosity LX∼1.9×1034 erg/s, while longer τD requires additional energy sources. The derived gravitational wave strain (h0∼10−29) remains undetectable with current instruments but constrains internal magnetic field geometries. This work highlights the critical role of magnetic inclination dynamics in pulsar spin-down behavior and offers a physically motivated framework that can be extended to other young neutron stars with measured magnetic inclination and braking indices.